A STUDY ON STABILITY ANALYSIS OF DUMPY SLOPE IN SURFACE COAL MINES - B.VISHVAKIRAN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
India is the second largest producer of coal in the world. The amount of coal produced even in unprecedented times of COVID-19 is 730.87mt. in which opencast mining is predominant method for such production. It is believed that production of coal may increase by 15-20% by 2021-2022. Such statistics indicate that large amount of waste dump is generated and handled. Unless proper scientific and methodological ways for handling of waste is followed, it would impose complex problems of coal recovery, mine safety and mining cost. Considering the major accidents, including disasters only due to slope failure, then there have been 23 accidents causing 143 fatalities from 1901 to 2016 (A.K. Dash). This statistic explains the importance of dump slope stability. The failure of dumps endangers men and machinery in a mine with a potential to cause catastrophic loss of life and property. Hence dump stability is critical in designing and functioning of any open cast mine. This project aims to study stability of dump slope with varying and modeling of such failures using SLOPE/W software. The factor of safety of each varied parameter is calculated and modeled